USULAN PERBAIKAN LAYOUT PRODUKSI OBLONG PADA DIVISI GARMEN LOKAL DI PT MKF, LTD. - Fendi, Fendi (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
Irregular layout of machinery in the local garment division at PT Mulia Knitting Factory Ltd. Has resulted in delay of transfer of materials therefore indirectly affecting production capacity This study aims the design new layout based on product material flow-shirts using routing sheets, priority scales, from to chart the cost, from to chart inflow, activity relationship charts, activity relationship diagram, and allocation activity diagram. The proposed layout of material handling is expected to enable the division to be more organized, lowering costs and increasing production capacity. Results show that daily transfer material handling costs has decreased into only 7% of the costs before the implementation of the new layout and production capacity has increased 8% compared to previous capacity.